If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -5 + 3w + -5 = 0 Reorder the terms: -5 + -5 + 3w + 3w = 0 Combine like terms: -5 + -5 = -10 -10 + 3w + 3w = 0 Combine like terms: 3w + 3w = 6w -10 + 6w = 0 Solving -10 + 6w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 6w = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 6w = 0 + 10 6w = 0 + 10 Combine like terms: 0 + 10 = 10 6w = 10 Divide each side by '6'. w = 1.666666667 Simplifying w = 1.666666667
| 2(x-2)/5+5x=10 | | 240/275 | | 4x-(x^2)=0 | | 55x=1 | | 11x^2-28x-15=0 | | 25a^2+60ab+36b^2-64=0 | | 3x/5-0.5+1.9 | | (15/1)/(-3/4) | | x=180-(90-x)-4 | | 6(x+2)+10x=8x+3(x-9) | | x=180-((90-x)-4) | | 15/1/-3/4 | | x/6-x+3/5=1 | | 6x+9=9x+3 | | r+5/3=-6 | | M-12=18 | | .75y-5=-.5y+4 | | .75y-5=-.5y+5 | | -0.5=d/9 | | 9t-6-6t=7 | | y/8+4=-15 | | 3(x-6)+8=5x-2 | | 2y^2-2y=84 | | 10z-3z-2=24-2z | | 10(3x-10)=4(5x-10) | | 3x/6-(x-2)/2=(x-1)/4 | | 10(3x-10)=4(5x+10) | | 4(3x-8)+9=12x-23 | | 36/(6/1-1/3) | | 7x+6x-1=0 | | 5z-8+2z=34 | | 45x+2155x-84=44(50x+55) |